PENGARUH PEMBERIAN BEASISWA TERHADAP PRESTASI BELAJAR MAHASISWA - Silvira Aditri Maharani; Buyung Surahman; Adam Nasution (Journal of Primary Education (JPE), 2024)
This research aims to determine the effect of providing scholarships on studentlearning achievement by looking at the cumulative achievement index betweenbefore and after receiving the scholarship. The type of research is quantitativeresearch, with data collection techniques used in the form of documentation. Thepopulation and sample are all students of the Elementary Madrasah TeacherEducation study program, Fatmawati Sukarno State Islamic University, Bengkulu whoreceived scholarships in 2023. The data analysis technique used is descriptiveanalysis using tables and t-tests. The results of the study indicate that there is aneffect of scholarships on student learning achievement. This is evidenced by theresults of the t-test with a sig coefficient of 0.000 <0.05. So it is hoped that thescholarship program in order to improve student learning achievement can continueto be implemented by expanding cooperation with scholarship-providinginstitutions.